Estudio de avifauna en el bosque de Mutzaguango, del barrio Chaupi Contadero, parroquia Belisario Quevedo, cantón Latacunga, provincia de Cotopaxi - Guanoluisa Tipantuña, Nataly Belen (2018)
In the project carried out in the Mutzaguango forest, in the Latacunga canton, Belisario Quevedo Parish, Chaupi Contadero neighborhood, it aims to study the avifauna present on the site; because it was observed that the site has the presence of birds; however, its status and description are unknown. Knowing the current state of the study area, it could be zoned according to the altitudinal gradient, based on the classification of ecosystems proposed by the Ministry of the Environment; therefore, two zones were established: the Arbustal Siempreverde Montano Del Norte De Los Andes middle zone (2000-3295 m.s.n.m) and the Arbustal Siempreverde and Herbazal del Páramo (3237 -3532 m.s.n.m) high zone. The birds were registered based on each one of the zones, establishing strategic points. The main methods and techniques used were the counting by points, the intensive search, direct observation and the photographic registry; which allowed the inventory of birds; determined in this way the richness of existing species in the place. In total 24 species, five orders and 12 families were identified.